ผลกระทบในเชิงกฎหมายและกระบวนการยุติธรรม เมื่อไม่มีกฎหมายบังคับใช้โดยเฉพาะกับปัญหาการบังคับสูญหาย - พิมลวิชยากิจ, ปณิธาน (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 30 No 3 (2562): Academic Services Journal, Prince of Songkla UniversityDO - 10.14456/asj-psu.2019.52, 2019)
บทความวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาถึงผลกระทบในเชิงบทบัญญัติทางกฎหมายและกระบวนการยุติธรรม จากกรณีที่สังคมไทยยังไม่มีบทกฎหมายที่จะนำมาบังคับใช้กับปัญหาการบังคับสูญหายเป็นการเฉพาะ โดยใช้การวิจัยเชิงคุณภาพ และใช้วิธีการสัมภาษณ์ในการเก็บรวบรวมข้อมูลจากมุมมอง ทัศนคติ และความคิดเห็นจากผู้ให้ข้อมูลสำคัญ สำหรับผู้ให้ข้อมูลสำคัญ คือ เจ้าหน้าที่หน่วยงานของรัฐ เจ้าหน้าที่องค์กรพัฒนาเอกชน ผู้เชี่ยวชาญทางด้านกฎหมาย และสมาชิกครอบครัวของผู้ที่หายสาบสูญจากกรณีที่คาดหมายว่าเป็นการบังคับสูญหาย จากผลการศึกษา พบว่า ผลกระทบในเชิงบทบัญญัติทางกฎหมายเมื่อไม่มีบทกฎหมายสำหรับบังคับใช้กับปัญหาการบังคับสูญหายเป็นการเฉพาะ คือ การบังคับสูญหายไม่เป็นการกระทำผิดทางอาญา และไม่มีการกำหนดมาตรการสำหรับการพิจารณาคดีที่มีลักษณะเป็นการบังคับสูญหาย เมื่อใช้บทบัญญัติและกระบวนการทางกฎหมายที่มีในปัจจุบันก็พบว่า ไม่สามารถนำมาปรับใช้กับการบังคับสูญหายซึ่งมีความซับซ้อนแตกต่างจากคดีอื่นได้ทั้งหมด นำไปสู่ผลกระทบในเชิงกระบวนการยุติธรรม คือ การที่ครอบครัวไม่มีสถานะเป็นผู้เสียหาย การที่ศาลมิได้ใช้อำนาจในการแสวงหาพยานหลักฐาน และการช่วยเหลือเยียวยาที่ไม่มีหลักเกณฑ์ที่ชัดเจน ทำให้การบังคับสูญหายยังคงมีอยู่เรื่อยไป จึงควรมีการบังคับใช้กฎหมายสำหรับการบังคับสูญหายเป็นการเฉพาะโดยเร็ว เพื่อให้เกิดมาตรการและกระบวนการในการแก้ไขปัญหาการบังคับสูญหายอย่างเหมาะสมและมีประสิทธิภาพ คำสำคัญ: การบังคับสูญหาย, เจ้าหน้าที่รัฐ   The objective of this article was to study the legal provisions and judicial process consequences from the case that Thai society does not have a specific law to enforce in enforced disappearances by using a qualitative research. The data was collected from perspectives, attitudes, and opinions from key informants by using an interview. The key informants were government officials, NGO staff, legal experts, and family members of those who have disappeared from the expected cases of enforced disappearance. The result of the study showed that the legal provisions and judicial process consequences from the case that Thai society does not have a specific law to enforce in enforced disappearances are that the enforced disappearances are not a criminal offense and there is no set of measures for judiciary that are enforced disappearances. When using the current legal provisions and judicial process consequences, it can not be applied to the enforced disappearance which is completely different from other cases. It leads to a judicial effect, since the family is not in injured person status, The court did not use the power to search for evidence, and the remedies do not have clear criteria. As a result, the enforced disappearances are still ongoing. Therefore, the laws should be enforced specifically for the enforced disappearances as soon as possible in order to have measures and procedures to solve the problem of enforced disappearances appropriately and efficiently. Keywords: enforced disappearance, state authorities